The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.33073/pjm-2020-001
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Salmonella Potential of New Lactobacillus Strains with the Application in the Poultry Industry

Abstract: Probiotics are considered an alternative to antibiotics in the prevention and treatment of Salmonella diseases in poultry. However, to use probiotics as proposed above, it is necessary to evaluate their properties in detail and to select the most effective bacterial strains in the application targeted. In this study, probiotic properties of new Lactobacillus sp. strains were investigated and their antimicrobial activity against 125 environmental strains of Salmonella sp. was determined using the agar slab meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 58 publications
1
8
0
5
Order By: Relevance
“…These results indicate the gut microbiota modulation effect of AC5 on Salmonella infection in chickens. Although the anti-inflammatory effect of probiotic Limosilactobacillus on Salmonella in other experimental models has already been investigated (Abhisingha et al, 2018;Mohanty et al, 2019;Shi et al, 2019;Smialek et al, 2019;Acurcio et al, 2020;Kanmani and Kim, 2020;Kowalska et al, 2020;Mizuno et al, 2020), the strain-specific effect of the probiotic plays a crucial role in their different outcomes. Liu et al (2018) showed that prophylactic oral feeding with L. plantarum and L. rhamnosus reduced Salmonella numbers and improved gut barrier integrity in C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate the gut microbiota modulation effect of AC5 on Salmonella infection in chickens. Although the anti-inflammatory effect of probiotic Limosilactobacillus on Salmonella in other experimental models has already been investigated (Abhisingha et al, 2018;Mohanty et al, 2019;Shi et al, 2019;Smialek et al, 2019;Acurcio et al, 2020;Kanmani and Kim, 2020;Kowalska et al, 2020;Mizuno et al, 2020), the strain-specific effect of the probiotic plays a crucial role in their different outcomes. Liu et al (2018) showed that prophylactic oral feeding with L. plantarum and L. rhamnosus reduced Salmonella numbers and improved gut barrier integrity in C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…enterica subspecies enterica ) is associated with the development of disease in warm-blooded animals. In the subspecies S. enterica , the serovars Enteritidis and Typhimurium are most prevalent both in humans and in poultry [ 55 , 56 ]. Salmonella enterica serovar Enteritidis is commonly associated with poultry and derived products, whereas serovar Typhimurium has a wider species range, affecting pigs and cattle as well as poultry [ 57 ].…”
Section: Salmonella Spp Infectionmentioning
confidence: 99%
“…However, other mechanisms are also involved in probiotic effects such as reduction in intraluminal pH due to production of short chain fatty acids, production of antimicrobial peptides, optimization of intestinal functionality and activation of immune response. Researchers tested single or multi-strain probiotics, in particular Lactobacillus , Enterococcus , and Bacillus strains, with encouraging results after a Salmonella challenge in chickens, considering parameters such as bacterial count in ceca, faecal bacterial load, growth performance, and immune functionality [ 56 , 66 , 67 , 68 , 69 , 70 , 71 ]. The effect of commercially available probiotic supplements such as EarlyBird ® (Pacific Vet Group USA Inc., Fayetteville, AR, USA) and FloraMax-B11 ® (Pacific Vet Group USA Inc., Fayetteville, AR, USA) alone, or with the addition of glycerol, was tested to obtain a protective effect against Salmonella Enteritidis colonization, demonstrating the prevention of intestinal colonization from the pathogen [ 72 , 73 ].…”
Section: Salmonella Spp Infectionmentioning
confidence: 99%
“…dalam menanggulangi infeksi Salmonella sp. dibagi menjadi 3 cara yaitu memproduksi asam laktat dan short-chain fatty acid (SCFA), berperan sebagai imunomodulator saat berinteraksi dengan sistem kekebalan tubuh dan bertindak sebagai physical barrier dengan melakukan kolonisasi (Menconi et al, 2011;Chen et al, 2012;Filho et al, 2015;Olnood et al, 2015;Ashayerizadeh et al, 2016;Nakphaichit et al, 2018;Kowalska et al, 2020).…”
Section: Formula Probiotikunclassified